Functional and radiological outcomes of primary ring fixator versus antibiotic nail in open tibial diaphyseal fractures: A prospective study. Issue 10 (October 2022) - Rohilla, Rajesh; Arora, Sahil; Kundu, Ankush; Singh, Roop; Govil, Vasudha; Khokhar, Arya
Abstarct: Background: Management of open fractures of tibia is still a matter of debate due to high incidence of infections. Traditionally external fixators have been advocated in managing open tibial fractures. Due to limited efficacy of systemic antibiotics, recently antibiotic coated intramedullary interlocking nails have been developed for the management of open tibia fractures. Therefore, we conducted this prospective randomized study to compare the functional and radiological outcomes of primary ring fixator versus antibiotic coated nail in open diaphyseal tibial fractures. Methods: The study included 32 patients with Gustilo-Anderson type II and type IIIA fractures of tibial diaphysis. Out of them 16 patients were managed with Ring External Fixator (Group I) and 16 were managed with Ossipro Ò gentamicin intramedullary interlocking tibial nail (Group II). The radiological and functional outcomes were assessed at final follow-up according to and SMFA criteria. Statistical analysis of the data was performed using IBM SPSS statistics 2.0 software. Chi square test and independent student t -test were used and a P value <0.05 was considered statistically significant Results: Union was achieved in 15 patients (93.8%) in group I and 13 patients (81.2%) in group II. Pin tract infection was seen in 6 patients (37.5%) in group I, whereas infection was present in 2 patients (12.5%) in group II. Bone results were excellent in 13 patients (81.3%), good in 2 patients (12.5%), poor in one patient (6.3%). In group II, bone results were excellent in 12 patients (75%), good in one patient (6.2%), poor in 3 patients (18.8%). At 1 year of final follow up, mean SMFA score was 24.41±5.87 in group I, whereas mean SMFA score was 23.703±8.02 in group II. Conclusion: Ring fixator as well as antibiotic coated tibial interlocking nail achieved comparable rates of union in the present study. Complication rates were similar in both the groups and the functional and radiological outcomes were comparable in both groups. Results of this study indicate that although ring fixation is an established option for management of open tibial fractures, antibiotic-coated intramedullary nail is also a reliable option in open Grade II and grade IIIA injuries. Level of Evidence: Level II.